2012
DOI: 10.3396/ijic.v8i3.027.12
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of efficacy of microwave oven irradiation in disinfection of patient derived dental cast

Abstract: The purpose of this study was to check the efficacy of household microwave oven irradiation in disinfection of dental gypsum casts obtained from patients. Impressions of upper arch of 10 volunteers were made using irreversible hydrocolloid. The casts were poured in type III gypsum. All casts were cut into two halves. One half of each cast was irradiated in a microwave oven , set at 650 W for a total of 3 minutes and the un-irradiated half was used as control. Suspension of casts was inoculated directly on Tryp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…Immersion disinfection ensures that all surfaces of the dental impression are exposed to the disinfectant; however, hydrocolloids and polyether materials cannot be immersed in disinfectants due to the imbibition phenomenon. Immersion disinfectants should be discarded after every use (except for glutaraldehydes) …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Immersion disinfection ensures that all surfaces of the dental impression are exposed to the disinfectant; however, hydrocolloids and polyether materials cannot be immersed in disinfectants due to the imbibition phenomenon. Immersion disinfectants should be discarded after every use (except for glutaraldehydes) …”
mentioning
confidence: 99%
“…Immersion disinfectants should be discarded after every use (except for glutaraldehydes). 12 The spray method of disinfection reduces the chance of distortion, especially in hydrocolloids and polyether, and also uses less disinfectant solution, but it may not reach the areas of undercuts and also releases air, leading to occupational exposure. 13 Antimicrobial agents have been incorporated into impression materials by the manufacturer, increasing the risk of dermal and mucosal irritation of the patient when multiple impressions are made.…”
mentioning
confidence: 99%
“…24 However, microwave energy levels as low as 650 W have been shown to disinfect stone casts contaminated by oral flora in three minutes. 25 Therefore, lower levels of microwave irradiation may be advisable for the safe disinfection of stone casts. …”
Section: Discussionmentioning
confidence: 99%
“…Another study revealed that the cast could be disinfected after five minutes of irradiation at 850 W (18). In the latter study, the disinfection of the casts contaminated by Bacillus subtilis following 10 minutes of irradiation was considered as sterilization effect of this method (18).…”
Section: Original Articlementioning
confidence: 99%
“…Since the microwave irradiation has been suggested for gypsum casts disinfecting, there are used in this context. Disinfection was reported by different irradiation techniques from one or two dry phase (10,(16)(17)(18)(19) to irradiation of the cast immersed in water18, within different times from 319 to 1018 minutes and applying different energy levels from 650 to 900 watts (W) (10,(16)(17)(18)(19). More studies have shown that applied lower levels of energy are safer for strength and accuracy of casts, than high levels and boiling the stone cast during the irradiation (17,(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%